Effect of Facebook-Based Learning on Students’ Performance in Educational Technology Concept - Issa, Ahmed Idris; Jibril, Mohammed; Onojah, Amos Ochayi; Onojah, Adenike Aderogba; Ekunola, Gbadebo Temitope (Indonesian Journal of Multidiciplinary Research, 2021)
This study investigated the effect of Facebook-based learning on the students’ academic performance. The study was a quasi-experimental using pre-test, post-test design which used for data collection from 30 colleges of education students forming the sample for the study. The performance test comprises of two different sets of objective questions. Multiple choice and completion test responses. The reliability coefficient of 0.75 was obtained from Kuder-Richardson (KR-20) formula for the multiple-choice test and Split-half reliability statistic was used to determine the reliability coefficient of the completion test responses which yielded 0.76. The research questions were answered using mean and standard deviation while paired sample t-test was used to test hypothesis 1 and independent sample t-test was used to test hypothesis 2. The findings of the study showed that there was a significant difference in the pretest and posttest performance of the Facebook-based group; and there was no significant difference in the performance of male and female students exposed to Facebook-based learning. The study concluded that the performance of the colleges of education students was enhanced when they are exposed to Facebook-based teaching methodology. It was recommended that colleges of education lecturers should be encouraged to adopt Facebook-based as an instructional strategy.